Secretory leukocyte protease inhibitor protects against severe urinary tract infection in mice - Anne L. Rosen; Michael A. Lint; Dayne H. Voelker; Nicole M. Gilbert; Christopher P. Tomera; Jesús Santiago-Borges; Meghan A. Wallace; Thomas J. Hannan; Carey-Ann D. Burnham; Scott J. Hultgren; Andrew L. Kau (mBio, 2024)
ABSTRACT Millions suffer from urinary tract infections (UTIs) worldwide every year with women accounting for the majority of cases. Uropathogenic Escherichia coli (UPEC) causes most of these primary infections and leads to 25% becoming recurrent or chronic. To repel invading pathogens, the urinary tract mounts a vigorous innate immune response that includes the secretion of antimicrobial peptides (AMPs), rapid recruitment of phagocytes, and exfoliation of superficial umbrella cells. Here, we investigate secretory leukocyte protease inhibitor (SLPI), an AMP with antiprotease, antimicrobial, and immunomodulatory functions, known to play protective roles at other mucosal sites, but not well characterized in UTIs. Using a preclinical model of UPEC-caused UTI, we show that urine SLPI increases in infected mice and that SLPI is localized to bladder epithelial cells. UPEC-infected SLPI-deficient (Slpi−/−) mice suffer from higher urine bacterial burdens, prolonged bladder inflammation, and elevated urine neutrophil elastase (NE) levels compared to wild-type (Slpi+/+) controls. Combined with bulk bladder RNA sequencing, our data indicate that Slpi−/− mice have a dysregulated immune and tissue repair response following UTI. We also measure SLPI in urine samples from a small group of female subjects 18–49 years old and find that SLPI tends to be higher in the presence of a uropathogen, except in patients with a history of recent or recurrent UTI, suggesting a dysregulation of SLPI expression in these women. Taken together, our findings show SLPI promotes clearance of UPEC in mice and provides preliminary evidence that SLPI is likewise regulated in response to uropathogen exposure in women.IMPORTANCEAnnually, millions of people suffer from urinary tract infections (UTIs) and more than $3 billion are spent on work absences and treatment of these patients. While the early response to UTI is known to be important in combating urinary pathogens, knowledge of host factors that help curb infection is still limited. Here, we use a preclinical model of UTI to study secretory leukocyte protease inhibitor (SLPI), an antimicrobial protein, to determine how it protects the bladder against infection. We find that SLPI is increased during UTI, accelerates the clearance of bacteriuria, and upregulates genes and pathways needed to fight an infection while preventing prolonged bladder inflammation. In a small clinical study, we show SLPI is readily detectable in human urine and is associated with the presence of a uropathogen in patients without a previous history of UTI, suggesting SLPI may play an important role in protecting from bacterial cystitis.